Materiais digitais no ensino de biologia: com a palavra, professores e licenciandos - Kapp, Alessandra Miguel (2022)
This research aimed to analyze how Biology teachers in high school at a federal institute and teachers in training for the Degree in Biological Sciences understand the role in teaching and the relevance of incorporating digital technologies into their educational practices, from the process of selection and use of digital technologies. To achieve the research objectives, we opted for qualitative research, which, when approaching different groups of participants – teachers and teachers in training – used the focus group as a data collection instrument. Two collection blocks were carried out with each group of participants, called GF.1 and GF.2. After organizing and rereading the data obtained, narratives were constructed, portraying the moment of discussion and reflection among the participants. We divided the categories built a posteriori into four axes: i) criteria for choosing digital materials; ii) forms of interaction with digital materials; iii) contributions of digital materials in biology classes; iv) limitations on the use of digital materials. As much as teachers in training and teachers have shown consensus with most of the categories presented above, the way of using and understanding the role of digital materials had a partially different character. Teachers in training highlighted the importance of an authorial production, articulated to educommunicative perspectives, although entirely restricted to the theoretical field, with proposals, not very systematized, of future works that teachers could develop in the classroom. When analyzing their practices during the internship regencies, the way of use fell to a more pragmatic character of illustration and demonstration of scientific knowledge. As much as they valued scientific quality when using the media, they pointed out insecurity when making good selections, considering the diversity of audiovisual productions available. However, we were able to identify, albeit initially, strategies for accessing, analyzing, and evaluating digital materials, aspects that approach media literacy. As limitations, they recognized difficulties related to the infrastructure of schools and the use of virtual spaces that transport students to possible problem situations that belong to "artificial" contexts. While most of the students' concerns were related to didactic aspects, the professors evaluated the selection criteria, the forms of interaction, the contributions, and the limitations based on processes that valued scientific knowledge. In this context, the videos gained many prominences, and the justifications were linked, for example, to the different possibilities of developing biological content, presenting micro perceptions within the biological field, and establishing faster relationships with the content to be treated in class. The focus group, little by little, also became a relevant space for reflection on the practice itself, promoting debates involving more contextualized biology teaching practices connected to contemporary challenges and in dialogue with educommunicative proposals. After experiencing the contributions of the focus group, we highlight the importance of expanding our studies to other contexts of initial and continuing teacher education to develop a more robust repertoire of scientific propositions linked to media literacy.